Women and temporality in literature and cinema : negotiating with timelessness - Ahlawat, Ila, 1989- (Amsterdam University Press, 2021)
Women and Temporality in Literature and Cinema delves into the subject of literary and cinematic women characters entrapped in temporal spaces and their peculiar communication with visibility, enclosure, space and time in the setup of a sexual and temporal discord. It explores subjects such as youth, ageing, remembering, forgetting, and repeating within the larger realm of gendered temporalities that are essentially a nuanced and affective experience.